The usefulness of circulating levels of leptin, kisspeptin, and neurokinin B in obese girls with precocious puberty. (3rd July 2018) - Kang, Min Jae; Oh, Yeon Joung; Shim, Young Suk; Baek, Joon Woo; Yang, Seung; Hwang, Il Tae
Abstract: This study investigated the relationships of circulating leptin, kisspeptin, and neurokinin B (NKB) levels with precocious puberty (PP) in overweight/obese girls and evaluated the usefulness of these markers in the initiation of puberty. One hundred and twenty-eight girls aged 7.0–8.9 years with PP (group A, normal-weight; group B, overweight/obese) and 30 age-matched normal controls (NC) were enrolled. Serum levels of leptin, kisspeptin, and NKB were measured by commercial kits. Serum leptin levels were higher in group A (4.21 ng/mL) and B (5.64 ng/mL) compared to the NC (2.35 ng/mL, p  < .001). Serum kisspeptin levels were lower in group A (0.59 ng/mL) than in group B (0.66 ng/mL, p  = .018). Serum NKB levels were not different among the three groups. The predictive value of leptin (AUC =0.791) was lower than that of IGF-1 (AUC =0.917, p  = .009), although both were significant markers for PP in the regression analysis. BMI z-score (AUC =0.806) was a predictive factor of PP. In conclusion, a higher level of leptin, IGF-1, and fatness in overweight/obese girls with PP compared to the NC confirms their roles in the regulation of puberty. Further research is needed if the effects of kisspeptin and NKB on puberty are limited at the levels of neurons or target tissue.